Mycelial Biomass Enzymes of Cordyceps militaris and Lentinula edodes in Baking Technology - Svetlana I. Koneva; Elena Yu. Egorova (Техника и технология пищевых производств)
Cordyceps militaris and Lentinula edodes are known for their high extracellular proteolytic, amylolytic, and laccase activity, which is important for bakery production. This article describes the effect of enzymes obtained from mycelial biomass of C. militaris and L. edodes on such properties of flour mixes as amylolytic and proteolytic enzymic activity during baking, technological costs, and bread quality. The research featured strains of C. militaris SRG4 and L. edodes 3790 fungi; mycelial biomass powder of these fungi on a sterile grain substrate (rice, wheat); experimental flour mixes of wheat bread and first-grade baking flour with mycelial biomass powder; bread made from the experimental flour mixes. The experimental part included standard methods used in the bakery industry. The mycelial biomass of C. militaris and L. edodes fungi proved to be a promising baking additive because it possessed hydrolytic enzymes and was rich in protein substances (32.2 ± 1.5 and 26.4 ± 2.0%, respectively), specific mushroom polysaccharides (36.7 ± 0.8 and 52.2 ± 1.2%, respectively), and carotenoids (1600 ± 40 mcg/g of C. militaris biomass). The active amylases and proteinases in the mycelial biomass powder improved the sugar-forming ability and reduced the falling number. In addition, they raised the amount of washed gluten with a slight decrease in elasticity, as well as provided an acceptable structure and viscosity of the dough at 1–4% of mycelial biomass powder. This dose resulted in an optimal bread formulation of standard quality. A bigger amount caused the crumb to darken and increased its humidity while reducing the specific volume. The bread samples with C. militaris were too acid. Mycelial biomass of C. militaris and L. edodes proved to be a good source of enzymes to be used with grain substrates in bakery production. Further research is needed to define the optimal dose and processing modes.